Trophic relationships between the crab Libinia ferreirae and its symbionts - Lemos Gonçalves, Geslaine Rafaela [UNESP] (2021)
Symbioses are ubiquitous in the animal kingdom. However, in most cases, the role of each member is relatively fixed, and it is rare for the same species to exhibit different symbiotic behaviours throughout its ontogeny. Here, we use stable isotope analyses of food resources to identify the relationships between the spider crab Libinia ferreirae as a symbiont of its jellyfish host during juvenile life stages and as a host for sea anemone epibionts on its carapace as an adult. We ask the following questions: How do the food sources used by the crab change between its juvenile and adult phase? How does the symbiotic relationship change when the crab develops from a juvenile into an adult? We were particularly interested in the extent to which L. ferreirae juveniles feed on jellyfish hosts versus planktonic prey during the juvenile symbiont phase and how adults feed on their epibionts during the free-living phase. δ13C of L. ferreirae differed between juvenile (associated with the jellyfish) and adult stages (free-living), unsurprisingly suggesting that there is little isotopic niche overlap between these life phases. SIMMr models using δ13C and δ15N of the crab and its potential food sources indicated that the juvenile crab symbionts did not derive any significant nutrition from medusae and relied predominantly on zooplankton prey. Since juvenile crabs do not have structures to capture zooplankton for feeding, we suggest that they may be kleptoparasites, stealing zooplankton food from their host, though further work is needed to identify the form that such a symbiosis might take. The nutrition of free-living crabs was predominantly derived from benthic algae and shrimps rather than from epibionts. These epibionts appear to use similar food resources as the host, suggesting a symbiotic relationship more akin to mutualism. Thus, the crabs move from a symbiosis in which they may act as parasites to one where they act as hosts. Such flexible approaches to symbioses may be more common than currently described, particularly in species with different functional roles during individual life stages.